Length and Depth Lateral Root of Jabon (Anthocephalus cadamba (Roxb.) Miq.) in Cibening District, Pamijahan, Bogor, West Java - Nurheni Wijayanto; Iftitah Rhahmi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Jabon (A. cadamba (Roxb.) Miq.) is one of forestry plants that be developed widely nowadays in planted forest or public forest. Jabon included in fast growing species with straight and cilindris stem. It can make Jabon is very intrested for raw material of wood industry. However rapid development of jabon have not been followed with land usage with agroforestry system. Land usage with agroforestry system with appropiate pattern can increase economical revenue and also can realize conservation activity of soil and water below the stand. setting of good planting pattern is affected by root system of plants. It is related with competition of nutrient absorption between main plant and agricultural plant. Beside that, root system also affect crown growth that continually affect on sun light availability, temperature, and humidityfor agricultural plants. This research aims to examine the length and depth of lateral root of jabon on mixture pattern and monocultural pattern. benefit of this research is for giving reference of agricultural species that is appropiate with root condition. The result showed that root system on mixture pattern has longerand deeper root than root on monocultural system. Setting of appropiate planting spaces between main plant with agricultural plant is very needed for avoiding nutrient copetition, water, and light.